Infective endocarditis and infected aneurysm caused by Streptococcus dysgalactiae subsp. equisimilis: a case report. Issue 2 (24th January 2017) - Watanabe, Naoki; Bandoh, Shuji; Ishii, Tomoya; Negayama, Kiyoshi; Kadowaki, Norimitsu; Yokota, Kyoko
Key Clinical Message: Endocarditis caused by Streptococcus dysgalactiae subsp. equisimilis (SDSE) is rare. Infected aneurysm is one of the most serious complications of infective endocarditis. However, no reports have described SDSE‐related infected aneurysm. We herein report a successfully treated case of SDSE‐associated infective endocarditis with an infected aneurysm. Abstract : Endocarditis caused by Streptococcus dysgalactiae subsp. equisimilis (SDSE) is rare. Infected aneurysm is one of the most serious complications of infective endocarditis. However, no reports have described SDSE‐related infected aneurysm. We herein report a successfully treated case of SDSE‐associated infective endocarditis with an infected aneurysm.